KONTRIBUSI PEMIKIRAN MAQASID SYARI'AH THAHIR IBNU ASYUR DALAM HUKUM ISLAM - Orien Effendi (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2020)
AbstractAs time goes by new problems in life always arise. Advances in science and technology have a profound influence on the problems of these new types in today's life. The provisions of Islamic law from previous thinkers seemed to be left behind if not immediately renewed to be able to keep up with the pace of development in times with increasingly diverse new problems. Of course there was nothing wrong with what the Muslim leaders had assembled at the time when formulating an Islamic law to solve the problem, at least what was compiled at that time could still be implemented right now, but a slight adjustment was needed in order to become Islamic law which has legal certainty both in its application as law in a particular group and in its application as public law.